BOT Contracts as One of the Legal Mechanisms to Encourage Investment in Alternative Energies - Atmania, Faiza; Nouiri, Souad (Journal of Legal Studies and Researches, 2024)
The BOT contract appeared as one of these contractual forms in which the state or one of its facilities gives the right over a facility or property to an investor. It is among the measures to achieve the established efforts to move towards sustainable development and create a clean environment as well as a new economy in accordance with what international and national circumstances require.